New insights into the potential cardioprotective effects of telmisartan and nanoformulated extract of Spirulina platensis via regulation of oxidative stress, apoptosis, and autophagy in an experimental model - Almukainzi, May; El-Masry, Thanaa A.; Ibrahim, Hanaa A.; Saad, Hebatallah M.; El Zahaby, Enas I.; Saleh, Asmaa; El-Nagar, Maysa M. F. (Frontiers in Pharmacology, 2024)
Background: Cardiotoxicity is one of the limiting side effects of the commonly used anticancer agent cyclophosphamide (Cyclo).Possible protective effects of telmisartan and nanoformulated Spirulina platensis (Sp) methanolic extract against Cyclo-induced cardiotoxicity were examined in this study. Experimental groups of the rats were randomly divided into nine groups: control vehicle, control polymer, telmisartan (TEL,10mg/kg), Free Sp extract (300mg/kg), Nano Sp extract (100mg/kg), Cyclo (200 mg/kg), respectively. Groups VII, VIII, and IX were treated the same as III, IV, and V groups, respectively, plus one dose of Cyclo on day 18.The results indicated that Cyclo caused significant cardiotoxicity as manifested by a notable increase (155.49%, 105.74%, 451.76% and 826.07%, respectively) in serum levels of glutamic oxaloacetic transaminase (SGOT), lactate dehydrogenase (LDH), creatine kinase MB (CK-MB) and cardiac troponin I (cTnI) enzyme activities in comparison to the control. In addition, cardiac glutathione (GSH) content, and activity of glutathione peroxidase-1 (GPX-1) enzyme were decreased (65.94%, 73.85%, respectively). Whereas, treatment with Nano Sp extract showed the most prominent restoration of the altered biochemical, histopathological, and immunohistochemical features compared with TEL and Free Sp. Also, a reduction (30.64% and 43.02%) in p-AKT content, and endothelial nitric oxide synthase (eNOS) immunoreactivity (60.43%, 75.30%) in relation to TEL and Free Sp-treated animals were detected. Interestingly, Nano Sp boosted autophagy signal via activation of beclin-1 (36.42%, 153.4%), LC3II (69.13%, 195%), and downregulating (39.68%, 62.45%) p62 expression along with increasing (90.3%, 225.9%) paraoxonase-1 (PON-1) gene expression in relation to TEL and Free Sp-treated animals, respectively.Sp extract against cardiotoxicity via activation of the antioxidant, antiapoptotic, and autophagy signaling pathways.